Associations between gut microbiome, short chain fatty acids and blood pressure across ethnic groups: the HELIUS study. (25th November 2020) - Verhaar, B; Collard, D; Prodan, A; Levels, J.H.M; Zwinderman, A.H; Snijder, M.B; Vogt, L; Peters, M.J.L; Muller, M; Nieuwdorp, M; Van Den Born, B.J.H
Abstract: Background: Gut microbiome composition is shaped by a combination of host genetic make-up and dietary habits. In addition, large ethnic differences exist in microbiome composition. Several studies in humans and animals have shown that differences in gut microbiota and its metabolites, including short chain fatty acids (SCFA), are associated with blood pressure (BP). We hypothesized that gut microbiome composition and its metabolites may be differently associated with BP across ethnic groups. Purpose: To investigate associations of gut microbiome composition and fecal SCFA levels with BP across different ethnic groups. Methods: We assessed the association between gut microbiome composition and office BP among 4672 subjects (mean age 49.8±11.7 years, 52%F) of 6 different ethnic groups participating in the HELIUS study. Gut microbiome composition was determined using 16S rRNA sequencing. Associations between microbiome composition and blood pressure were assessed using machine learning prediction models. The resulting best predictors were correlated with BP using Spearman's rank correlations. Fecal SCFA levels were measured with high-performance liquid chromatography in an age- and body mass index (BMI)-matched subgroup of 200 participants with either extreme low or high systolic BP. Differences in abundances of best predictors and fecal SCFA levels between high and low BP groups were assessed with Mann-Whitney U tests. Results: Gut microbiome composition explained 4.4% of systolic BP variance. Best predictors for systolic BP included Roseburia spp. (ρ −0.15, p<0.001), Clostridium spp. (ρ −0.14, p<0.001), Romboutsia spp. (ρ −0.10, p<0.001), and Ruminococceae spp. (ρ −0.15, p<0.001) (Figure 1). Explained variance of the microbiome composition was highest in Dutch subjects (4.8%), but very low in African Surinamese, Ghanaian, and Turkish ethnic groups (ranging from 0–0.77%) Hence, we selected only participants with Dutch ethnicity for the matched subgroup. Participants with high BP had lower abundance of Roseburia hominis (p<0.01) and Roseburia spp. (p<0.05) compared to participants with low BP. However, fecal acetate (p<0.05) and propionate (p<0.01) levels were higher in participants with high BP. Conclusions: In this cross-sectional study, gut microbiome composition was moderately associated with BP. Associations were strongly divergent between ethnic groups, with strongest associations in Dutch participants. Intriguingly, while Dutch participants with high BP had lower abundances of several SCFA-producing microbes, they had higher fecal SCFA levels. Intervention studies with SCFAs could provide more insight in the effects of these metabolites on BP. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): The Academic Medical Center (AMC) of Amsterdam and the Public Health Service of Amsterdam (GGD Amsterdam) provided core financial support for HELIUS. The HELIUS study is also funded by research grants of the Dutch Heart Foundation (Hartstichting; grant no. 2010T084), the Netherlands Organization for Health Research and Development (ZonMw; grant no. 200500003), the European Integration Fund (EIF; grant no. 2013EIF013) and the European Union (Seventh Framework Programme, FP-7; grant no. 278901).